2020
DOI: 10.1177/1367006920914399
|View full text |Cite
|
Sign up to set email alerts
|

L2 proficiency predicts inhibitory ability in L1-dominant speakers

Abstract: Aims and Objectives: Bilinguals reportedly perform better in tasks that require the suppression of interference because of the constant practice in linguistic inhibition. However, previous literature was largely based on comparisons of pure monolinguals and balanced bilinguals. Those in between the two extremes were rarely examined. This project aimed at studying whether the population who primarily speak in a first language with a different level of second language proficiency also enjoy bilingual advantage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 67 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…It has been suggested that a strong L2 (i.e., higher proficiency) is assumed to elicit a stronger interference on the L1 as compared to a weak L2 (i.e., lower proficiency), leading to increased cognitive demands (e.g., inhibitory control; Green, 1998;Hui, Yuan, Fong & Wang, 2020;Lehtonen et al, 2018). Given that bilingualism is a continuous and dynamic process, it could be possible that monolingualbilingual differences could only be observed when bilinguals reach certain level of L2 proficiency (Vega-Mendoza et al, 2015).…”
Section: The Role Of Language Proficiency In Bilingualismmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that a strong L2 (i.e., higher proficiency) is assumed to elicit a stronger interference on the L1 as compared to a weak L2 (i.e., lower proficiency), leading to increased cognitive demands (e.g., inhibitory control; Green, 1998;Hui, Yuan, Fong & Wang, 2020;Lehtonen et al, 2018). Given that bilingualism is a continuous and dynamic process, it could be possible that monolingualbilingual differences could only be observed when bilinguals reach certain level of L2 proficiency (Vega-Mendoza et al, 2015).…”
Section: The Role Of Language Proficiency In Bilingualismmentioning
confidence: 99%
“…The effects of language proficiency on executive control were examined by comparing performance on these abovementioned cognitive tasks of high and low-proficient bilinguals to monolinguals. We predicted that monolingual-bilingual differences would be more likely to be observed between high-proficient bilinguals and monolinguals, while low-proficient bilinguals took an intermediate position (Hui et al, 2020;Vega-Mendoza et al, 2015).…”
Section: The Current Studymentioning
confidence: 99%
“…There have been a few recent studies concerning the relationship between language proficiency and bilingual inhibitory control (e.g., Bosma et al, 2017;Boumeester et al, 2019;Hui et al, 2020;Iluz-Cohen & Armon-Lotem, 2013;Poarch, 2018;Poarch & van Hell, 2012;Singh & Mishra, 2012, 2013Wang et al, 2016;Yow & Li, 2015). However, similar studies on trilingualism have not been found.…”
Section: Bilingual/multilingual Inhibitory Control and Language Profi...mentioning
confidence: 99%
“…Similarly, Wang et al (2016) administered the Simon arrow task in adult Mandarin learners of English with high and low proficiency in L2, finding that high-proficiency learners outperformed low-proficiency peers in interference suppression observed with the bivalent Simon arrow tasks. Most recently, Hui et al (2020) using a Stroop task investigated the relationship between L2 proficiency and inhibitory control ability in L1-dominant speakers with different degrees of proficiency in L2. They also found that L2 learners with higher proficiency performed significantly better in response inhibition in the Stroop task.…”
Section: Introductionmentioning
confidence: 99%
“…We used the color-word Stroop test, which requires subjects to inhibit a highly automatic task while focusing attention on a less automatic one [ 41 , 42 ] and the social facilitation paradigm. Stroop interference (SI), a measure of the cost of resolving the conflict between the distractor and the task, has been shown to be inversely correlated with the cognitive advantage: the greater the advantage, the lower the SI [ [43] , [44] , [45] , [46] ]. The study used SI to quantify the advantage in two groups of bilingual participants which differed in the level of L2 proficiency (high vs. low L2 proficiency).…”
Section: Introductionmentioning
confidence: 99%